Socialization Of Legal Awareness To Students In SMAS Kartika VII-2 Kendari - Arifai, Arifai; Lanontji, Muryanto; Akib, Ma'ruf (Amaliah: Jurnal Pengabdian Masyarakat, 2017)
In life in the community and school can not be separated from the rules that apply, both written rules and unwritten rules. These rules must be fully complied with. The existence of these rules is to create prosperity and justice in the community. If these rules are violated, there will be strict sanctions. As written above, there are still many people in Indonesia who violate laws or regulations. Many of the rules that have been agreed upon and written down are still being violated. This is not only in government circles, the community, but also spreads to agencies including educational institutions or schools. Community Service Grants (HPM) Universitas Muhammadiyah Kendari (UMK) in the form of Legal Awareness Socialization for Students on Domestic Violence (KDRT) which was held at SMAS Kartika VII-2 Kendari which was attended by a combination of grade XII IPA 1, 2 and 3 as many as 62 people accompanied by BK teachers, this activity went very well which began with the presentation of material by resource persons on the study of the Law on Domestic Violence & Child Abandonment, dissect cases of domestic violence and child association in Kendari City then continued with interactive question and answer and communicative. With the Community Service Grant (HPM) program carried out by the Implementing Team in the form of socialization at SMAS Kartika VII-2 Kendari, it can provide legal education materials related to laws and regulations regarding Legal Awareness for Students including Domestic Violence (KDRT) and Child Abandonment. With the provision of socialization, legal awareness forms the mindset, behavior patterns and attitudes of students at SMAS Kartika VII-2 Kendari to be more disciplined so that the knowledge that has been received can become the forerunner of law-aware students in the school environment and not only that, become a pilot project for schools in Kendari City in particular and generally in Southeast Sulawesi Province.